2018
DOI: 10.1186/s12879-018-3148-z
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities and co-medications in populations with and without chronic hepatitis C virus infection in Japan between 2015 and 2016

Abstract: BackgroundDirect-acting anti-viral agents have improved the treatment of chronic hepatitis C virus (HCV) infection, but this treatment is challenging for patients using co-medications because of potential drug–drug interactions. This study aimed to examine the comorbidities and co-medications of Japanese chronic HCV patients by age group, compared with a non-HCV patient population.MethodsThis was a retrospective observational study using a hospital-based medical claims database. We extracted data of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 24 publications
1
17
9
1
Order By: Relevance
“…We also did not find evidence of increased prevalence of any cardiovascular conditions among people with HCV compared to the general population, including both acute (myocardial infarction, stroke) or chronic (hypertension, chronic coronary syndrome, congestive heart failure, arrhythmia) conditions. This is in contrast to other studies that found increased prevalences of these conditions among people with HCV [10,12,13,16], although, again, our condition ascertainment was more rigorous. Again, we note that the comparator studies used a variety of ascertainment methods for defining comorbidity, the majority of which have not been validated, or included symptom-based diagnoses such as pain, making comparisons challenging.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…We also did not find evidence of increased prevalence of any cardiovascular conditions among people with HCV compared to the general population, including both acute (myocardial infarction, stroke) or chronic (hypertension, chronic coronary syndrome, congestive heart failure, arrhythmia) conditions. This is in contrast to other studies that found increased prevalences of these conditions among people with HCV [10,12,13,16], although, again, our condition ascertainment was more rigorous. Again, we note that the comparator studies used a variety of ascertainment methods for defining comorbidity, the majority of which have not been validated, or included symptom-based diagnoses such as pain, making comparisons challenging.…”
Section: Discussioncontrasting
confidence: 83%
“…This was true for conditions known to have causal relationships with HCV, including diabetes, some cancers, and chronic renal failure [5][6][7], although our estimates for these conditions were generally lower than those in other studies with less stringent, unvalidated methods of chronic disease ascertainment [10,13,14,16] or from clinical charts. [11] We also found greater prevalence of lung conditions including asthma and COPD, which were, when combined, higher than some [10,13] and lower [16] than prevalences reported in studies with less robust definitions, likely due to overlap between these conditions and their relationship with smoking. We also did not find evidence of increased prevalence of any cardiovascular conditions among people with HCV compared to the general population, including both acute (myocardial infarction, stroke) or chronic (hypertension, chronic coronary syndrome, congestive heart failure, arrhythmia) conditions.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…These studies showed significant comorbidities such as diabetes, dyslipidaemia and hypertension amongst HCV patients, but did not report on multiple comorbidities. Liu et al [28] reported on multiple comorbidities in their study of Taiwanese adult HCV patients using a physician-completed survey, as did Ruzicka et al [29] in their study of Japanese adult HCV patients using a medical claims database and Louie et al [30] in their study of patients with chronic HCV using a US medical claims database. All of these studies showed a significant prevalence of multiple comorbidities (e.g., more than 50% of Japanese HCV patients had ≥4 comorbidities, and 52% of US patients reported [6][7][8][9][10][11][12][13][14][15], with the latter two showing this to be greater than amongst matched controls (e.g., only 29.5% of Japanese non-HCV patients had ≥4, and over 47% of US patients reported ≤5 comorbidities).…”
Section: Introductionmentioning
confidence: 95%
“…Their study confirmed the potential impact of coexisting diseases and multiple medications on the efficacy of treatment and highlighted the research gap in developing treatment policies that take both factors into account. Research groups led by Utz and Ruzicka [16,17] investigated the difficulty of treatment for patients with Gaucher disease Type 1 and chronic hepatitis C virus, respectively. Both studies emphasized the need to optimize medication treatment strategies for such complex diseases.…”
Section: Related Workmentioning
confidence: 99%